Arctic Policies of Non-Arctic States - Dervovic, Medy,; Kirchner, Stefan,; Ulatowski, Laura, (International Law E-books Online, Collection 2026., 2025)
This edited book offers updated, novel, and multidisciplinary perspectives on the Arctic policies of non-Arctic States, including those less frequently addressed in academic literature. While most chapters delve into existing Arctic policies, some explore Arctic policies in the making. Each contribution provides a combination of historical accounts, explanations of selected non-Arctic States' interests in the Arctic, as well as discussions regarding their Arctic policies and role in Arctic law and governance. As such, Arctic Policies of Non-Arctic States covers, in alphabetical order, Belgium, China, Greece, Japan, Latvia, the Netherlands, Spain, and includes one general perspective on Asian States.